2016
DOI: 10.1007/s40618-016-0499-4
|View full text |Cite
|
Sign up to set email alerts
|

The pre-mir-27a variant rs895819 may contribute to type 2 diabetes mellitus susceptibility in an Iranian cohort

Abstract: Our study shows that rs895819 in hsa-mir-27a is associated with T2DM susceptibility and that the C allele conveyed a protective role against T2DM. Larger multicentric and specific functional studies will be necessary to obtain a deeper comprehension of the role of rs895819 and hsa-mir-27a and how they are involved in the development of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…Therefore, wild miR-27a may have a protective role against obesity and hence T2DM. It is conceivable that more active miR-27a (with the CC genotype) has a more protective role against T2DM as reported in previous studies [55,71]. Nevertheless, Wang et al 2015 have never observed the protecting effect of miR-27 against T2DM in the Chinese Han population [77].…”
Section: Mir-27a Rs895819mentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, wild miR-27a may have a protective role against obesity and hence T2DM. It is conceivable that more active miR-27a (with the CC genotype) has a more protective role against T2DM as reported in previous studies [55,71]. Nevertheless, Wang et al 2015 have never observed the protecting effect of miR-27 against T2DM in the Chinese Han population [77].…”
Section: Mir-27a Rs895819mentioning
confidence: 88%
“…The rs895819 has been reported to be associated with decreased risk to T2DM in Italian and Iranian populations [55,71]. It has been suggested that rs895819T>C increased the expression of the miR-27a [55,[71][72][73]. It has been demonstrated that miR-27 exerts a negative effect on adipogenesis [74].…”
Section: Mir-27a Rs895819mentioning
confidence: 99%
“…We also observed strong correlations in subcutaneous adipose after gastric bypass and weight loss between miR‐27a‐5p and GLUT4 and NLRP3 mRNA and between NLRP3 protein levels and miR‐22 and miR‐24‐2‐5p (Figure ). miR‐27a‐5p has not been implicated in the regulation of NLRP3 to date, but miR‐27a was reported to play a role in insulin resistance by regulating GLUT4 signaling along with miR‐106b and miR‐30d ; a single‐nucleotide polymorphism in the pre‐27a miRNA is reported to be associated with T2D .…”
Section: Discussionmentioning
confidence: 99%
“…We also observed strong correlations in subcutaneous adipose after gastric bypass and weight loss between miR-27a-5p and GLUT4 and NLRP3 mRNA and between NLRP3 protein levels and miR-22 and miR-24-2-5p ( Figure 6). miR-27a-5p has not been implicated in the regulation of NLRP3 to date, but miR-27a was reported to play a role in insulin resistance by regulating GLUT4 signaling along with miR-106b and miR-30d (34); a single-nucleotide polymorphism in the pre-27a miRNA is reported to be associated with T2D (35,36). Given the role of inflammation in metabolic dysfunction, we were particularly interested in exploring the obesity-associated inflammasome NLRP3 (15) as an experimentally validated target of miR-223-3p (37).…”
Section: Discussionmentioning
confidence: 99%
“…75 Ghaedi et al performed a study with 413 Iranians (204 T2DM, 209 healthy controls) and found that the C allele of miR-27a rs895819 was more frequently distributed in the control group and played a protective role against the developmental process of T2DM. 76 In addition, Wang et al found that the CC genotype of miR-27a rs895819 was significantly associated with the increased risk of T2DM in the obese group (24 ≤ body mass index ≤ 28). 75 Ciccacci et al demonstrated that the G allele of miR-27a rs895819 had a protective effect against the development of T2DM.…”
Section: Relationship Between Mirnas Snps and T2dmmentioning
confidence: 99%